ANALISIS PENDALAMAN DAN PENGEMBANGAN MATERI FIKIH PADA PEMBELAJARAN PAI DI MADRASAH TSANAWIYAH - Fauzil Ihya Husaini; Ahmad Jauhari; Mahyuddin Barni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The teaching of Fiqh at the Madrasah Tsanawiyah (MTs) level plays a crucial role in shaping students’ understanding, attitudes, and skills in practicing Islamic teachings. However, social dynamics and advances in digital technology require a deeper exploration and innovation of Fiqh curriculum to better align with the context and needs of students. This study aims to present the deepening of Fiqh curriculum at the MTs level and to examine strategies for curriculum development that align with contemporary developments. This study employs a literature review approach by collecting and analyzing various relevant sources of literature regarding the MTs Fiqh curriculum and efforts to develop it. The research findings indicate that Fiqh curriculum at MTs is structured progressively, covering aspects of purification and worship in Grade 7, social and spiritual worship in Grade 8, and muamalah (transactions) and funeral procedures in Grade 9. The development of Fiqh curriculum materials can be achieved through a contextual approach, the implementation of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models, the utilization of digital technology and artificial intelligence (AI), the reinforcement of religious moderation values, and the enhancement of teachers’ competencies. These various approaches can make the study of Fiqh more meaningful, practical, and responsive to the challenges of modern life. Therefore, the development of Fiqh curriculum materials must be carried out on an ongoing basis to improve the quality of learning and to nurture students who are religious, critical, moderate, and of good character.